2010
DOI: 10.1103/physrevb.82.014414
|View full text |Cite
|
Sign up to set email alerts
|

Coupling between magnon and ligand-field excitations in magnetoelectricTb3Fe5O12garnet

Abstract: The spectra of far-infrared transmission in

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 23 publications
(49 reference statements)
1
13
1
Order By: Relevance
“…31 In our recent study of the far-IR excitations in Tb-IG we observed a coupling between magnons and ligand field electronic excitations of Tb 3+ and suggested that the tuning of the dielectric constant by temperature and magnetic field can be connected to the appearance of the hybrid magneto-electric modes. 4 In contrast, in the present studies of Dy-IG we found a stronger connection between the static dielectric constant and the spectra of the optical phonons (see Section VI of this paper). Also, we recently reported an observation of hybridization between electric-and magnetic-dipole activity for the ligand-field excitations, which was only possible due to the combined analysis of the transmission, reflection, and RAE spectra of Dy-IG.…”
Section: Far-ir Excitations In Re-igcontrasting
confidence: 54%
See 1 more Smart Citation
“…31 In our recent study of the far-IR excitations in Tb-IG we observed a coupling between magnons and ligand field electronic excitations of Tb 3+ and suggested that the tuning of the dielectric constant by temperature and magnetic field can be connected to the appearance of the hybrid magneto-electric modes. 4 In contrast, in the present studies of Dy-IG we found a stronger connection between the static dielectric constant and the spectra of the optical phonons (see Section VI of this paper). Also, we recently reported an observation of hybridization between electric-and magnetic-dipole activity for the ligand-field excitations, which was only possible due to the combined analysis of the transmission, reflection, and RAE spectra of Dy-IG.…”
Section: Far-ir Excitations In Re-igcontrasting
confidence: 54%
“…2 Formation of the local electric polarization induced by the magnetic ordering was also observed in Tb-IG. 3 These reports were followed by far-IR spectroscopic studies of the coupling between magnons and ligand-field excitations in Tb-IG in the temperature range of ~ 70 K. 4 These results bring up a number of new questions about the interconnection between the crystal and magnetic structure with the far-IR optical excitations in the related R-IGs compounds, such as Dy-IGs.…”
Section: Introductionmentioning
confidence: 99%
“…[70] and Supplemental Material [51]). Magnon excitations could provide decay channels analogous to electronic excitations [67], given constraints due to momentum and energy transfer.…”
Section: Pr 3+ Cefsmentioning
confidence: 99%
“…Then, by hybridization, a magnetoelectric CF excitation can transfer its electro-activity to a magnon. This mechanism was already proposed in HoMn 2 O 5 and Tb 3 Fe 5 O 12 from FIR measurements [30,31]. In order to test the validity of this scenario in ErMnO 3 , the Er 3+ (J=15/2) CF levels were calculated using a point charge model [32,33], taking into account the 7 O 2− closer neighbors of the two Er sites, with screening factors [34], fitted to recover the experimentally identified CF levels.…”
mentioning
confidence: 99%